THE IMPACT OF PREMIUM INCOME ON ASSET GROWTH: A CASE OF INDONESIA SHARIA INSURANCE - Purnama Sari, Warsani; Rosalina, Dhian; Laili KS, Isnaniah (Accounting and Business Journal, 2020)
This study evaluate the premium income rate on asset growth of Sharia Insurance companies that registered in the Indonesian Financial Services Authority. The type of research used in this study is comparative causal method. The sample used are 20 sharia insurance companies with the criteria of sharia insurance companies that are actively operating for the last three years. The results of this study indicated that the level of premium income positively and significantly affect the growth of sharia insurance asset growth. This acpect predictly change the consumer behaviour of takaful sharia insurance on how they allocate their fund. This study is concerned with the level of premium income that affects the growth of Sharia Insurance assets in Indonesia.